Management of Carpal Tunnel Syndrome – Surgical Vs Medical? - Kuddus, Md Ruhul; Faruk, Md Omar; Alam, Samiul; Islam, KM Atiqul; Alam, Shamsul; Debnath, Hadadhan (Bangladesh Journal of Neurosurgery, 2020)
Background: Carpal Tunnel Syndrome (CTS) is the most common form of entrapment neuropathy. Both the Medical and surgical treatments are popular in the management of CTS. The effectiveness of the surgical treatment of carpal tunnel syndrome (CTS) is well known on short term. Surgical approach has proved to be more efficient relative to the conservative methods of steroid injections and splinting. On the other hand, many studies have demonstrated both advantages and adverse effects of the surgical methods. However, limited data is available about long-term outcome after carpal tunnel release (CTR). So debate is still persists regarding Conservative vs. Surgical approach to treatment of CTS. Methods: A retrospective analysis of 15 consecutive cases performed during 1.5 year was conducted. 8 patients were treated surgically with transpalmar approach. 7 patient were treated conservatively. The criteria for treatment efficacy were improvements in symptoms, such as pain, paresthesia and recurrences after surgery. Results: Female were predominant 80% than male 20%. Right hand was more frequently affected 80% than left 20%. most paitents were diabetic except 2. outcome in the surgical group was excellent. Patient of non-surgical group was not satisfied as surgical group. Conclusions: CTR is a robust treatment for CTS and its effect persists after a period of years. CTR is the choice of treatment in case of moderate to severe form of CTS. Long term follow up and inclusion of more cases is needed for a definite conclusion. Bang. J Neurosurgery 2020; 10(1): 75-81